The Crisis of the Judicial Reform Law in Israel in 2023 And the Israeli and American Positions on It (Journal of Misan Researches, 2025)
Justice Minister Yariv Levin, in Benjamin Netanyahu's sixth government, submitted a Basic Law to the Knesset that would allow the Knesset to overturn any judicial decision by the Supreme Court. The move sparked public and official reactions and divisions in Israel, nearly leading to a civil war. The law also impacted Israel's relations with the United States, which refused to pass the law. This forced the Israeli Prime Minister to suspend the law. Given the importance of this event, it was chosen as a topic for research.